2021
DOI: 10.7759/cureus.18427
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Progressive Dyspnea: Lymphocytic Interstitial Pneumonia in Collagen Vascular Disease

Abstract: We describe an interesting rare case of a 61-year-old woman who was admitted to our hospital for exertional dyspnea, non-productive cough, and generalized weakness of six months duration. Her computed tomography was significant for ground-glass opacities combined with bibasilar consolidations and numerous pulmonary cysts. There can be a significant overlap in imaging findings of post-coronavirus disease 2019 (COVID-19) lung disease and interstitial lung disease from autoimmune diseases. We review in extensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…[ 7 ] As in other diffuse interstitial lung diseases, lung high-resolution CT is the radiological method of choice to determine the lung manifestations of LIP, with multiple bronchial cysts and diffuse interstitial infiltrates as its characteristic manifestations, [ 8 ] and studies have found ground-glass shadows lobular centers or small subpleural nodules, thickened bronchovascular bundles, thickened lobular septa and cysts as well. [ 3 , 9 , 10 ] The formation of a thin-walled cystic lumen may be associated with progressive obstruction and dilatation of the airway by lymphocytes infiltrating around the fine bronchi. [ 11 ] Misdiagnosis and missed diagnoses can easily occur with imaging alone, and the combined use of several diagnostic methods can improve its diagnostic accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…[ 7 ] As in other diffuse interstitial lung diseases, lung high-resolution CT is the radiological method of choice to determine the lung manifestations of LIP, with multiple bronchial cysts and diffuse interstitial infiltrates as its characteristic manifestations, [ 8 ] and studies have found ground-glass shadows lobular centers or small subpleural nodules, thickened bronchovascular bundles, thickened lobular septa and cysts as well. [ 3 , 9 , 10 ] The formation of a thin-walled cystic lumen may be associated with progressive obstruction and dilatation of the airway by lymphocytes infiltrating around the fine bronchi. [ 11 ] Misdiagnosis and missed diagnoses can easily occur with imaging alone, and the combined use of several diagnostic methods can improve its diagnostic accuracy.…”
Section: Discussionmentioning
confidence: 99%